1984
DOI: 10.1016/0304-3959(84)90018-6
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal thermography in the evaluation of chronic back pain: A comparative study

Abstract: This research involves the relative value of liquid crystal contact thermography (LCT) as compared to the physical examination, myelography, electromyography and CT scanning in the examination of 155 chronic low back pain patients. Thermograms were interpreted by two independent examiners as positive for nerve root compromise. Results demonstrate excellent interobserver reliability when used for this specific purpose and respectable correlations with the physical examination and EMG studies were obtained. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, widespread adoption of such technology is limited by high capital costs, motion artefacts and inability for use outside of clinical or laboratory settings. Other low-cost thermography techniques have been explored for potential screening of deep venous thrombosis [4][5][6][7] , breast cancer [8][9][10] , spinal root syndromes 11,12 , chronic back pain 13 and even pulmonological diagnostics 14 . Recent work 15,16 demonstrates that electronic temperature-mapping devices can be constructed in ultra-thin, soft and compliant formats, sometimes referred to as 'epidermal' due to the similarity of their physical characteristics to those of the skin itself.…”
mentioning
confidence: 99%
“…However, widespread adoption of such technology is limited by high capital costs, motion artefacts and inability for use outside of clinical or laboratory settings. Other low-cost thermography techniques have been explored for potential screening of deep venous thrombosis [4][5][6][7] , breast cancer [8][9][10] , spinal root syndromes 11,12 , chronic back pain 13 and even pulmonological diagnostics 14 . Recent work 15,16 demonstrates that electronic temperature-mapping devices can be constructed in ultra-thin, soft and compliant formats, sometimes referred to as 'epidermal' due to the similarity of their physical characteristics to those of the skin itself.…”
mentioning
confidence: 99%
“…Percentage of correspondence with myelography and CT were substantially lower, 54% and 58%, respectively. According to findings, liquid crystal contact thermography showed some promise as an adjunctive diagnostic tool in the assessment of chronic back pain patients with radicular symptoms, especially where further surgery is contemplated and the more structural tests of CT scanning and myelography may be falsely positive as a result of previous back surgery (Newman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of Zhao trail, in addition to the emphasis on the role of temperature difference in the diagnosis of benign and malignant head and neck cancer, the obtained accuracy rate declared the diagnosis value priority of this tool in comparison with other methods (Zhao et al, ). But another study, in which contact thermography was used to diagnosis chronic back pain, demonstrated the low value of diagnosis and recommended this method could be applicable as a complementary diagnostic test (Newman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of LCT was later extended to identifying painful varicocele. 77 LCT has also shown promise 78 as an additional diagnostic tool in the assessment of back pain where alternative techniques may lead to falsely positive results due to previous surgery. A later study 79 reported a reduced usefulness of the technique in revealing nerve root compression in lumbosacral lateral spinal stenosis.…”
Section: Review Of Lct As An Investigative and Diagnostic Tool In Medmentioning
confidence: 99%